Analyzing and comparing customer waiting time in road transport department office using queuing theory model and simulation model / Noor Hidayah Mohd Zaki ... [et al.] - Mohd Zaki, Noor Hidayah; Ismanuddin, Aina Nabila; Mahusin, Siti Nur Amimah; Mohamad Yusuf, Asmahanim (Universiti Teknologi MARA Cawangan Pahang, 2020)
Waiting for service or also known as queuing is a frequently occurring phenomenon. People queue for services at various place such as at the hospitals, banks, post offices and many more. However, long and unmanaged queues may cause dissatisfactions among the customers thus will affect the customers' evaluation of the services. Not only that, time will also be wasted since people need to wait for hours before being served. Other than that, every organization has their time limit in serving their customers. Due to this limitation, it leads to overcrowding and unmanageable queues at the premise. Ensuring this, queuing theory model has been applied for the selected situation in Road Transport Department located in Senawang, Negeri Sembilan. One of the main objectives was to analyze and compare the customer waiting time queuing model to simulation model. M/M/s queuing model was performed on the collected data and simulation with ARENA software was used to build and verify the result. It is concluded that the best method to measure the queuing situation is by using ARENA simulation model since the result is more accurate than Queuing Theory Model.